Influence of Cerium on the Reduction Behaviour of Iron Oxide by Using Carbon Monoxide: TPR and Kinetic Studies - Tengku Saharuddin, T.S.; Nor Azman, N.S.E.; Salleh,F.; Samsuri,A.; Othaman,R.; Kassim,M.; Mohamed Hisham,M.W.; Yarmo,M.A. (Universiti Sains Islam Malaysia, 2024)
Reduction of iron oxide is one of the most studied topics owing to the importance of iron/steel industry and also has been used as a precursor and active component in a number of important chemical processes. The interaction between iron oxide and other metal additive have gained interest in the past two decades due to the ability on enhancing the reduction performance of the iron oxide. Therefore, this study was undertaken to investigate the influence of cerium on the reduction behaviours of iron oxide by (10%, v/v) carbon monoxide in nitrogen. The cerium doped (Ce-Fe2O3) and non-doped iron oxide reduction behaviour and the kinetic studies have been studied by temperature programmed reduction (TPR) and the phases formed of partially and completely reduced samples were characterized by X-ray diffraction spectroscopy (XRD) while the activation energy values were calculated from Arrhenius equation using Wimmer's method. TPR results indicate that the reduction of doped and undoped iron oxide proceeds in three steps reduction (Fe2O3 ? Fe3O4 ? FeO ? Fe), while doped iron oxide showed a large shifted towards lower temperature especially in the transition steps of FeO ? Fe. Furthermore, TPR results also suggested that by adding Ce metal into iron oxide the reduction of metal iron completed at lower temperature (700 ?C) compared to non-doped iron oxide (900 ?C). Meanwhile, XRD analysis indicated that doped iron oxide composed of Fe2O3 and a small amount of FeCe2O4. The increase in the rates of iron oxide reduction may relate to the presence of cerium species in the formed of FeCe2O4 and was confirmed by the decrease in the activation energy regarding to all transition phases (Fe2O3 ? Fe3O4 ? FeO ? Fe) during the reduction process